Peran Mahkamah Konstitusi dalam Menjaga Keseimbangan Kekuasaan: Analisis terhadap Putusan MK tentang Batas Usia Capres dan Cawapres - Padan Batari Siregar; Dika; Muhammad Ibnu Adha; Ach Farhanuddin Kamil; Ade Fartini (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
This research discusses the role of the Constitutional Court (MK) in maintaining the balance of power through an analysis of Constitutional Court Decision No. 90/PUU-XXI/2023 regarding the minimum age requirement for presidential and vice-presidential candidates. The study employs a qualitative approach using the library research method, drawing from legal documents, scholarly literature, and relevant constitutional sources. The findings indicate that the Constitutional Court holds a strategic position as the guardian of the constitution, ensuring the implementation of the checks and balances principle within Indonesia’s constitutional system. However, in the context of this decision, the Court is viewed as having extended its authority beyond the legislative domain. The ruling sparked debates over judicial independence and its implications for democracy. Therefore, the Court must uphold integrity, transparency, and accountability to remain a neutral, authoritative institution devoted to constitutional justice.